Corona-Tagebücher / Dzienniki covidowe: Contents and introduction - Ewa Mikulska-Frindo; Magdalena Bieniasz (The Central European Review of Economics and Management (CEREM), 2023)
[Editorial note:] We are proud to present the results of the "Translation project Covid diaries at WSB Merito University in Wrocław". As the editor of this volume, Ewa Mikulska-Frindo, writes, in March 2020 the "Literaturhaus Graz" invited 19 writers to keep Covid Diaries. The full version of the diaries, published between 11 March and 28 July 2020, counts 700 pages. Selected texts were translated by students of the WSB Universities in Wrocław as a part of a study project. This is a rather untypical issue of the Central European Review of Economics and Management. With the kind agreement of the "Literaturhaus Graz", we publish parts of the Corona Diaries (Die Corona-Tagebücher) in their original German version and their Polish translation. While normally the language of publication is English, we consider this a good occasion to make a small contribution to the popularization of German-language literature in Poland.
Keywords: 330